(untitled) (Third Sector Social Economic Review, 2017)
The purpose of this study is to reveal the effect of psychological capital on postponement behaviors of 80 nurses’ survey working in two private hospitals in business in Nevşehir. According to the research findings, it has been determined that the dimensions of hope, self-efficacy, optimism and endurance which are the sub-dimension of psychological capital do not have a significant effect on job postponement behaviour.